(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
This study aimed to learn about the effects of listening to gangster rap music. The researchers observed that music could be found almost anywhere, and it can easily be accessible via radios, various recordings, the internet, and new technologies; however, according to the studies, music could highly influence our behavior. The researchers specified that music could cause young audiences to behave badly. Furthermore, researchers have found out that the more you listen to gangster rap music, the more it can affect your lifestyle, the way you talk, your outfit, and your use of curse words. With proper parenting and giving advice as to what music they should avoid, their children would grow to know what music is bad for them. The researchers would like to recommend this study to Generation Z, who are prone to this kind of music, to be conscious of what music they should listen to because it could influence their behaviors, as well as future researchers, in order to expand this study case the participants to know more bout this study. Overall, the discussion in this subsection emphasizes the importance of being mindful of the music we listen to and the potential influence it can have on our behavior.